The application of arbuscular mycorrhizal fungi to micropropagation systems : an opportunity to reduce chemical inputs - Hooker, John E.; Gianinazzi, Silvio; Vestberg, Mauritz; Barea, Jose M.; Atkinson, David (Agricultural Research Centre of Finland, 1994)
The application of arbuscular mycorrhizal fungi to micropropagation systems: an opportunity to reduce chemical inputs. Agricultural Science in Finland 3: 227-232. (1Soil Biology Unit, Land Resources Department, Mill of Craibstone, Bucksburn, Aberdeen, AB2 9TS, UK, 2 INRA-CNRS, Laboratoire de Phytoparasitologie, Station de Génétique et d'Amelioration des Plantes, INRA, BV 1540, F-21034 Dijon Cedex, France, 3 Agricultural Research Centre of Finland, Laukaa Research and Elite Plant Unit, FIN-41340 Laukaa, Finland, 4 CSIC, Estación Experime ntal del Zaidin, Departmento de Microbiologia, Prof Albareda I, E-18008 Granada, Spain, 5 SAC, West Mains Road, Edinburgh EH9 3JG, UK.)
COST working group meeting on micropropagation and mycorrhiza.
Nimekkeen selvennys: Arbuskelimykorritsasienten käyttö mikrolisätyillä kasveilla: mahdollisuus vähentää kemiallisten lannoitteiden käyttöä.
Keywords: micropropagation; sustainability